Dilemma of Natural Death While Scuba Diving. Issue 2 (June 2013) - Sadler, Charlotte A.; Nelson, Craig; Grover, Ian; Witucki, Peter; Neuman, Tom
Sudden death from natural causes occurs frequently and the cause is often not discovered until the time of autopsy. Just as it occurs on land, so too do natural deaths occur in the water. However, the deaths may be inappropriately attributed to drowning simply due to their occurrence in the water, particularly in the case of scuba divers. We emphasize the importance of taking into consideration all factors when investigating these deaths, with particular emphasis on witness statements, equipment analysis, and autopsy findings in attempt to avoid the mischaracterization of sudden natural death in the water as drowning. We present two cases of sudden death in middle-aged males while scuba diving. Upon close examination of the autopsy findings, in conjunction with the eyewitness statements regarding the circumstances of their deaths, the cause of death was ultimately determined to be due to their significant cardiac disease, rather than drowning. In cases such as these, particular importance must be given to heart weight, evidence of coronary artery disease, lung weights, and evidence of aspiration on autopsy. If the evidence suggests death due to cardiac disease, these deaths should be categorized as natural deaths and not drownings.